PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT MCDERMOTT INDONESIA BATAM - Haironi, Rita; Lestari, Tri; Huzaimah, Arne (BENING, 2023)
The aim of this research is to determine the influence of compensation, work environment, and job satisfaction on the performance of PT McDERMOTT Indonesia Batam employees. The population in this study was 1026 employees, with the employees used as samples determined using the Slovin formula, obtaining a sample of 92 employees. The analytical method used is multiple linear regression analysis, and the research results show that simultaneously the compensation variables, work environment, and job satisfaction have a significant effect on employee performance, and partially the compensation variables, work environment, and job satisfaction have a significant effect on employee performance. From the research results it is also known that the job satisfaction variable has a dominant influence on the performance of McDERMOTT Indonesia Batam employees.